Sintering behavior of triol sol-gel derived Nb-doped PZT ceramics: Effects on phase, microstructure and electrical properties - Sangsubun C. (2014)
The ceramicswere fabricated from nano-sizedNb-doped PZT powder, whichwas synthesized by a triol sol-gel method. The powder was pressed and sintered at the temperature in between 900-1250°C for 2-6 h with heating/cooling rates of 5-20°C min-1. The XRD results showed that increasing the sintering temperature caused phase changes from dominate rhombohedral to co-existence of tetragonal and rhombohedral phases which can be observed at the sintering temperature up to 1000°C. In addition, changes of heating rate and holding time also affected phases presented in the ceramics. SEM micrographs showed small grain with a diameter of ∼0.3 μm occurred at 900°C. The uniform grain size of ∼1 μm was found at temperature above 1000°C. Grain growth behavior was dominant at 1200°C as the grain size increases to ∼5 μm. The optimum sintering condition for Nb-doped PZT ceramics was found to be 1100°C with a heating rate of 5°C min-1 for a 6 h dwell time. This condition provided the ceramic with density ∼ 95%, a uniform grain size distribution with an average grain size of 1.7 μm, a remnant polarization of 20.4 μC cm-2 and a coercive field of 7.6 kV cm -1. Copyright © Taylor & Francis Group, LLC.